Synthesis and Characterization of a Hybrid Cement Based on Fly Ash, Metakaolin and Portland Cement Clinker - Barboza Chávez, Adriagni Carolina; Gómez Zamorano, Lauren Yolanda; Acevedo Dávila, Jorge Leobardo (Molecular Diversity Preservation International, 2020)
Hybrid cement has become one of the most viable options in the reduction of CO2 emissions to the environment that are generated by the cement industry. This could be explained by the reduction of the content of clinker in the final mixture and substitution of the remaining percentage with supplementary cementitious materials with the help of an alkaline activation. Following that, properties that are provided by an Ordinary Portland Cement and of a geopolymer are mixed in this type of hybrid material and could be achieved at room temperature. Thereafter, the main objective of this research was to synthesize hybrid cements reducing the clinker content of Portland Cement up to 20% and use metakaolin and fly ash as supplementary cementitious materials in different proportions. The mixtures were alkaline activated with a mixture of sodium silicate and sodium hydroxide, calculating the amounts according to the percentage of Na2O that is present in each of the activators. The samples were then characterized using Compressive strength, X-ray diffraction, Fourier Transform Infrared Spectroscopy, and Scanning Electron Microscopy with energy-dispersive X-ray spectroscopy. The results indicated that the hybrid cements have similar mechanical properties than an Ordinary Portland Cement, and they resulted in a dense matrix of hydration products similar to those that are generated by cements and geopolymers.